Haemophilus paraphrophilus brain abscess in a 9-year-old boy: Case report and literature review - Hind ZRIKEM; Loubna AIT SAID; Kawtar ZAHLANE (Hasanuddin University, 2020)
Human diseases due to A. paraphrophilus aren’t usual. The following case report describes the first isolated case of A. paraphrophilus brain abscess in our laboratory. A 9-year-old boy presented to pediatric emergencies for frontal headache, vomiting, blurred vision and left hemiparesis. Radiological diagnosis consists with a frontal abscess. Gram staining of purulent samples showed abundant neutrophils with gram negative bacilli. Culture was made on blood agar, chocolate agar, Chapman’s agar and incubated in 5% CO2 at 37°C for 24 hours. Positive culture was detected only on chocolate agar. It was monomicrobial with small yellowish non-hemolytic colonies. Gram stain of colonies showed pleomorphic gram-negative coccobacilli. The strain required V factor for growth. The isolated strain was sensitive to all antibiotics tested. The interest of this case is that it shows the emergence of A. paraphrophilus as a causative agent of brain abscesses on pediatric population without associated congenital heart disease. It may also help identifying risk factors of these infections and how to prevent them.